Effect of direct adrenaline infusion into isolated rat heart on the induction of ventricular tachyarrhythmias - Aksu, Ahmet Davut; Hložková, Jana; Ríos, Gerardo Enrique Abarca; Malek, Mohammed Naeem; Panovský, Roman; Groszek, Grażyna; Mokrý, Petr; Kepák, Tomáš; Scheer, Peter; Sepši, Milan (MethodsX, 2025)
•In this study, hearts from 72 male Wistar albino rats were divided into two main protocols: a 40 min ischemia group (protocol A, n = 53) and 10 min ischemia group (protocol B, n = 19). Protocol A subdivided into 2 groups as a control group (n = 10) and adrenaline group (n = 43). Protocol B is subdivided into 2 groups as control group (n = 10) and adrenaline group (n = 9). Both adrenaline groups received the same dose of adrenaline.•In protocol A, ventricular tachyarrhythmia (VTA) incidence was 0 % in controls but rose to 72 % in the adrenaline group (p < 0.01). Heart rates for the control and adrenaline groups in stabilization and reperfusion were 254±45 bpm and 247 ± 66 bpm, versus 277 ± 41 bpm and 651 ± 286 bpm, respectively.•In protocol B, VTA incidence reached 100 % in both groups during reperfusion, with heart rates of 393 ± 29 bpm and 892±227 bpm for controls and 350 ± 49 bpm and 949 ± 116 bpm for the adrenaline group.•These findings suggest that direct adrenaline administration into the heart in last 5 mins of the ischemic period and the 5 mins of in the reperfusion time increases the incidence of reperfusion-induced ventricular arrhythmias up to 72 % in protocol A. Protocol B hearts showed reperfusion-induced ventricular arrhythmias with 100 % incidence in both groups.
Keywords: Reperfusion injury; Reperfusion arrhythmias; Langendorff apparatus; Direct adrenaline protocol; Epinephrine; Regional ischemia